The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1128/aem.07351-11
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Biosynthetic Operon for the Antibacterial Peptide Herbicolin in Pantoea vagans Biocontrol Strain C9-1 and Incidence in Pantoea Species

Abstract: ABSTRACTPantoea vagansC9-1 is a biocontrol strain that produces at least two antibiotics inhibiting the growth ofErwinia amylovora, the causal agent of fire blight disease of pear and apple. One antibiotic, herbicolin I, was purified from culture filtrates ofP. vagansC9-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 50 publications
3
42
0
Order By: Relevance
“…The sequencing results showed that the bacterial community included 10 types of pathogenic bacteria, including seven E. cloacae strains, K. oxytoca , 20 E. billingiae , and P. vagan 21 . This study confirmed that pathogenic bacteria exist in the traditional Chinese medicine Shenqu.…”
Section: Discussionsupporting
confidence: 60%
“…The sequencing results showed that the bacterial community included 10 types of pathogenic bacteria, including seven E. cloacae strains, K. oxytoca , 20 E. billingiae , and P. vagan 21 . This study confirmed that pathogenic bacteria exist in the traditional Chinese medicine Shenqu.…”
Section: Discussionsupporting
confidence: 60%
“…genomes was used for determination of the biocontrol-specific genes in P. vagans C9-1 and P. agglomerans E325. As expected for P. vagans C9-1, the herbicolin I and pantocin A gene clusters were indicated as singletons (43,44,107). The antibiotic biosynthesis gene cluster of P. agglomerans E325 was identified from the list of singletons for this strain and …”
Section: Application Of Genomics To Improve Fire Blight Management Bisupporting
confidence: 69%
“…P. vagans C9-1 was reported to produce a second antibiotic, called herbicolin I [17], but lately renamed dapdiamide E [27]. The chemical structure was described recently for P. agglomerans 48b/90 with the indication that P. vagans C9-1 also produced this compound [28], but the biosynthetic genes of this antibiotic were not identified.…”
Section: Resultsmentioning
confidence: 99%
“…Plasmid rescue and sequencing of the insertion site in mutant CIR624 indicated that the insertion took place in a hypothetical gene, encoded on pPag2 in a cluster containing several predicted biosynthetic and hypothetical genes. Analysis of the insertions that are present in the proposed dapdiamide E biosynthetic cluster is underway [27].…”
Section: Resultsmentioning
confidence: 99%